Biomedical ethics (McGraw-Hill, 2001)
This best-selling anthology of readings with case studies provides insightful and comprehensive treatment of ethical issues in medicine. Appropriate for courses taught in philosophy departments as well as in schools on medicine and nursing, the collection covers provocative topics such as conflicts of interest in medicine, advance directives, physician-assisted suicide, and the rationing of health care. The effective pedagogical features include chapter introductions, argument sketches, explanations of medical terms, headnotes, and annotated bibliographies.